Experimental study to analyze the effectiveness of reclaimed asphalt pavement aggregates in asphalt mix design - Azhar Falak; Habib Noor Zainab (E3S Web of Conferences)
The addition of reclaimed asphalt pavement aggregates (RAP) to hot-mix asphalt is a fast-growing potential solution towards the reduction of unfavorable environmental and economic effects of using virgin aggregates during pavement construction. Particularly within the United Arab Emirates, the process of using RAP in new pavement construction is still quite unpopular due to strict limitations and resulting performance concerns. This investigative study utilized RAP material that was obtained from a pavement site located in the city of Abu Dhabi. Following UAE specification guidelines, a 15% RAP inclusive blend was created to effectively explore how the presence of RAP can influence the HMA mix, by comparing the blend to a baseline mixture, which consisted of all natural aggregates with no RAP percentage. The tests that were performed on both samples were inclusive of maximum density, Marshall stability and flow, percentage voids in mineral aggregates, and percentage of voids filled with asphalt. The resultant data clearly indicated that RAP presence does not in any way cause a decline in the HMA mix properties in terms of Marshall properties. Nevertheless, it is still critical to carry out an analysis of the effects that a further increase in RAP percentage will have on an HMA mix, and to also carry out an investigative study regarding the economic benefits of utilizing RAP aggregates in pavement construction.